La construction du Maghreb au défi du partenariat euro-méditerranéen de l’Union européenne - Abdelwahab Biad (L’Année du Maghreb)
The article analyzes and evaluates the experience of Maghreb integration in terms of the interaction of endogenous and exogenous factors that influence it , the most important of which being relations with Europe. The authors’ suggest that Maghreb commitment to the goals and objectives of the Euro-Mediterranean Partnership has perverse effects, most notably by becoming a substitute for real cooperation and regional integration as envisaged by the Marrakech Treaty establishing the UMA. The article notes first, the failure of cooperation among members of a «community of destiny» unable to define itself in either economic or political terms and confronted by various technical barriers which impede progress towards Maghreb integration. The article then proposes an analysis of the interaction between construction of a Maghreb identity and the attraction of Europe, raising the question of whether this attraction has not become a substitute for the former, with the unspoken hope of establishing a synergy between the two strategies. On this last point, the author suggests the European Union’s Euro-Mediterranean partnership should focus on southern integration, which, together with good governance would ensure stability in the region.